Suppressor of max2 1-like 5 promotes secondary phloem formation during radial stem growth - Wallner, Eva-Sophie; Tonn, Nina; Shi, Dongbo; Jouannet, Virginie; Greb, Thomas (The plant journal, 2020)
As a pre-requisite for constant growth, plants produce vascular tissues at different sites within their post-embryonic body. Interestingly, the formation of vascular tissues during longitudinal and radial expansion of shoot and root axes differs fundamentally with respect to its anatomical configuration. This raises the question to which level regulatory mechanisms of vascular tissue formation are shared throughout plant development. Here, we show that, similar to primary phloem formation during longitudinal growth, the cambium-based formation of secondary phloem depends on the function of SUPPRESSOR OF MAX2 1-LIKE (SMXL) genes. In particular, local SMXL5 deficiency results in the absence of secondary phloem. Moreover, the additional disruption of SMXL4 activity increases tissue production in the cambium region without secondary phloem being formed. Using promoter-reporter lines, we observed that SMXL4 and SMXL5 activities are associated with different stages of secondary phloem formation in the Arabidopsis stem. Based on genome-wide transcriptional profiling and expression analyses of phloem-related markers, we concluded that early steps of phloem formation are impaired in smxl4;smxl5 double mutants and that the additional cambium-derived cells fail to establish phloem-related features. Our results showed that molecular mechanisms determining primary and secondary phloem formation share important properties, but differ slightly with SMXL5 playing a more dominant role in the formation of secondary phloem.
Published online 7 January 2020
Gesehen am 29.11.2021